Characteristics of Summer Precipitation around the Western Ghats and the Myanmar West Coast. (4th March 2015) - Shrestha, Dibas; Deshar, Rashila; Nakamura, Kenji
Abstract : Characteristics of summer (June–August) precipitation over two coastal mountain regions in South Asia (Western Ghats: WG and Myanmar West Coast: MWC) with a focus on topographic impact are analyzed using the 13-year (1998–2010) high spatial resolution (0.05° × 0.05°) version 6 data obtained from the Tropical Rainfall Measuring Mission (TRMM) Precipitation Radar (PR). A relationship between precipitation patterns and topography was observed in the coastal mountains. In both the WG and MWC, maximum rainfall along a tight line on the upwind side of the coastal mountains is primarily attributed to rain frequency. However, intense precipitation was observed over the offshore regions. Compared with the WG, deeper and large-scale precipitation systems develop over the MWC, producing more intense rainfall. It is suggested that insufficient humidity deters large-scale convection over the WG, and the atmosphere is sufficiently moist over the MWC.